Why Do Lazy People Make More Money? The Strange Case of the Public Sector Wage Premium - Ugo Panizza (Inter-American Development Bank, Office of the Chief Economist, 1999)
Empirical work suggests the presence of a public sector wage premium, the reasons for which are investigated in this paper. The results demonstrate a higher premium paid to women and premium decreases concurrent with skills. Job security undermines the incentive to work hard and forces the public sector to pay higher wages. Thus, the public sector wage premium can be used as an indicator of inefficiency in the public sector.
Keywords: 330; Lohn; Öffentlicher Sektor; Effizienzlohn; Theorie; Lateinamerika; OECD-Staaten